The Role of TNF-α (Tumor Necrosis Factor-alpha) in Pulmonary Tuberculosis - Sulistyasmi, Wiwit; Fuzianingsih, Eka Noviya; Kuncara, Rachmad Bayu (Academic Hospital Journal, 2025)
Background: Tuberculosis (TB) remains a primary global health concern, with Indonesia accounting for approximately 10% of international cases. Tumor necrosis factor-alpha (TNF-α) plays a crucial role in the immune response against Mycobacterium tuberculosis, particularly in pulmonary tuberculosis (TB).Method: This article is a narrative literature review that examines the role of tumor necrosis factor-alpha (TNF-α) in pulmonary tuberculosis.Result:  This pro-inflammatory cytokine is essential for activating macrophages, promoting phagolysosome fusion, and supporting the formation and maintenance of granulomas—immune structures critical for containing infection. However, dysregulated TNF-α expression can be detrimental: excessive levels contribute to inflammation and lung tissue damage, while insufficient production—such as that induced by TNF-α inhibitor therapy—can lead to reactivation of latent TB. This narrative review examines the biosynthesis, immunological functions, and regulatory mechanisms of TNF-α in the context of pulmonary tuberculosis, highlighting its dual role in protective immunity and immunopathology.Conclusion: A deeper understanding of TNF-α modulation may inform the development of targeted, host-directed therapies that improve treatment outcomes while minimizing tissue damage.